Computer Generated Hologram without Photography - Jamal, Raid (Iraqi Journal of Science, 2025)
In this paper we obtained Fourier transformation hologram that it has relativelyhigh efficiency by using Personal Computer, laser printer, transparence paperwithout need to use the conventional photography process. Matlab program used toobtain hologram. Optical and Computerized reconstruction process was done on it.The results show this method is promising it is important to present it to researchersand students that they are working in all optics laboratories.